2021
DOI: 10.1111/cch.12819
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rational‐emotive education on irrational thinking, subjective wellbeing and self‐efficacy of typically developing students and social acceptance of disabled students

Abstract: Aim This study aimed to assess the effects of rational‐emotive education on the rational thinking, subjective well‐being and self‐efficacy of typical students and their levels of social acceptance of disabled students in mainstream classrooms. Background Rational‐emotive education exercises can be important for eliminating typical students' problem behaviours, such as poor acceptance of disabled classmates, in mainstream classrooms. Method The study was conducted between 25 October 2017 and 17 January 2018 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, it is differentially attractive to people according to physical activity levels, BMI, age, and cultural [ 26 ]. Moreover, the lack of face-to-face guidance, supervision, and timely feedback may result in less effective learning outcomes for students in online teaching [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is differentially attractive to people according to physical activity levels, BMI, age, and cultural [ 26 ]. Moreover, the lack of face-to-face guidance, supervision, and timely feedback may result in less effective learning outcomes for students in online teaching [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the virtual learning environment requires more self-discipline and initiative from students ( 38 , 39 ). The lack of classroom atmosphere and real-time teacher guidance may make students’ learning effectiveness somewhat affected ( 40 ). A previous study has noted that students found it difficult to clear doubts in online teaching and more students believed they had better learning experience with face-to-face learning ( 35 ).…”
Section: Introductionmentioning
confidence: 99%